Politics of Marginalization: How Caste Affects Political Career of Dalits in Nepal - Nepali, Ghamber (Dhaulagiri Journal of Sociology and Anthropology, 2024)
Dalit leadership thrives only on the inclusive policies and practices of political parties in a diversified society. This study explores how the caste system affects the political career of Dalits in Nepal by means of the author’s autoethnography and in-depth interviews taken with Dalit political leaders and activists. The study reveals that the caste system plays a key role in accessing and controlling the power politics of Dalit leaders and activists. The influence of caste prevails among political parties, from grassroots to top leadership. The high-caste domination is not only prevalent in the institutional structures of conventional parties but also in the communist parties. Besides, the Dalit politicians have frequently faced untouchability from non-Dalits while conducting party activities in their parties, and private and public spaces. To overcome the caste hegemony, this paper suggests the deconstruction of the caste system that will lead to the liberation of Dalits.